The Effect of Benzyl Amino Purine (BAP) Concentration on the Growth Amount of the Explant of Dendrobium spectabile Orchid by In-Vitro - Ario Ario; Setiawan Setiawan (STKIP Singkawang, 2020)
Dendrobium spectabile orchid is an ornamental plant of high economic value, having relatively durable properties, beauty, and attractiveness of orchids lie in the diverse shapes and colors of the flowers. Therefore, it requires rapid and efficient propagation techniques. One of them is in-vitro vegetative propagation. Plant propagation using the in-vitro technique has the opportunity to produce a large number of plant seeds in a relatively short time. This study aims to determine the correct concentration of Benzyl Amino Purine (BAP) on the growth amount of the explants of Dendrobium spectabile orchid by in-vitro. The research was conducted at the Biotechnology Laboratory of the Regional Technical Implementation Unit (UPTD) of the Aloe Vera Center (AVC) Pontianak. This research was conducted from January 1, 2020, to March 30, 2020. The method used was a Completely Randomized Design (CRD). The treatment consisted of 6 levels of treatment, namely b1 = 0.75 ppm, b2 = 1.00 ppm, b3 = 1.25 ppm, b4 = 1.50 ppm, b5 = 1.75 ppm, b6 = 2.00 ppm. All treatments were repeated 4 times for each treatment consisting of 3 plant samples. The research finding showed that the treatment of BAP concentration 1.50 was the best in increasing the average number of leaves 4.92 strands, the average number of shoots 4.25 buds, and the average leaf length was 2.44 cm.